Pendampingan Remaka Dengan Youth Learning Community Model Di Paroki Santo Gabriel Pulang Pisau - Stefanus Stefanus; Fransiskus Janu Hamu; Agnes Angi Dian Winei (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
This study aims to offer a model of mentoring the youth learning community in the Santo Gabriel Pulang Pisau Parish. The model is called the Youth Learning Community in assisting youth at Santo Gabriel Pulang Pisau Parish, as a means of cultivating the development of youth faith. This study also describes previous assistance used for mentoring youth at the Santo Gabriel Pulang Pisau Parish. This research uses a qualitative approach with descriptive methods. The research data was obtained using interviews conducted with 4 youths, 1 Senior OMK, 1 Catechist and 1 Priest. The data obtained was analyzed with the benefit of the